Existing Approaches to Chemical, Biological, Radiological, and Nuclear (CBRN) Education and Training for Health Professionals: Findings from an Integrative Literature Review - Kako, Mayumi; Hammad, Karen; Mitani, Satoko; Arbon, Paul (Prehospital and Disaster Medicine, 2018)
This review was conducted to explore the literature to determine the availability, content, and evaluation of existing chemical, biological, radiological, and nuclear (CBRN) education programs for health professionals. An integrative review of the international literature describing disaster education for CBRN (2004-2016) was conducted. The following relevant databases were searched: Proquest, Pubmed, Science Direct, Scopus, Journals @ OVID, Google Scholar, Medline, and Ichuschi ver. 5 (Japanese database for health professionals). The search terms used were: "disaster," "chemical," "biological," "radiological," "nuclear," "CBRN," "health professional education," and "method." The following Medical Subject Headings (MeSH) terms, "education," "nursing," "continuing," "disasters," "disaster planning," and "bioterrorism," were used wherever possible and appropriate. The retrieved articles were narratively analyzed according to availability, content, and method. The content was thematically analyzed to provide an overview of the core content of the training. The literature search identified 619 potentially relevant articles for this study. Duplicates (n=104) were removed and 87 articles were identified for title review. In total, 67 articles were discarded, yielding 20 articles for all-text review, following 11 studies were retained for analysis, including one Japanese study. All articles published in English were from the USA, apart from the two studies located in Japan and Sweden. The most typical content in the selected literature was CBRN theory (n=11), followed by studies based on incident command (n=8), decontamination (n=7), disaster management (n=7), triage (n=7), personal protective equipment (PPE) use (n = 5), and post-training briefing (n=3). While the CBRN training course requires the participants to gain specific skills and knowledge, proposed training courses should be effectively constructed to include approaches such as scenario-based simulations, depending on the participants' needs. Kako M , Hammad K , Mitani S , Arbon P . Existing approaches to chemical, biological, radiological, and nuclear (CBRN) education and training for health professionals: findings from an integrative literature review. Prehosp Disaster Med. 2018;33(2):182-190.